Chromium(iii)-based potential molecular quantum bits with long coherence times - Lenz, Samuel; Bamberger, Heiko; Hallmen, Philipp P; Thiebes, Yannick; Otto, Sven; Heinze, Katja; van Slageren, Joris (Physical chemistry chemical physics : PCCP, 2019)
Molecular quantum bits based on copper(ii) or vanadium(iv) have been shown to possess long coherence times on multiple occasions. In contrast, studies in which non-spin-½ ions are employed are relatively scarce. High-spin ions provide additional states that can be used to encode further quantum bits. Furthermore, an optical rather than a microwave readout of molecular quantum bits is highly desirable, because in principle it could allow addressing at the single quantum bit level. The chromium(iii) complex [Cr(ddpd)2]3+ (ddpd = N,N'-dimethyl-N,N'-dipyridine-2-yl-pyridine-2,6-diamine) combines both the large spin (S = 3/2) and optical activity (strong, long lived luminescence). Here we demonstrate that the compound possesses coherence times of up to 8.4(1) μs, which are much longer (at least three times) than those for other chromium(iii)-based compounds. On the other hand, it is proved to be impossible to read out or influence the quantum state by optical means, underlining that further work is needed in this direction.